A Spectrophotometric Study on Light Attenuation Properties of Dental Bleaching Gels: Potential Relevance to Irradiation Parameters - Eugenia Anagnostaki; Valina Mylona; Kyriaki Kosma; Steven Parker; Marianna Chala; Mark Cronshaw; Vasilis Dimitriou; Michael Tatarakis; Nektarios Papadogiannis; Edward Lynch; Martin Grootveld (MDPI AG, 2020)
Background: During in-office bleaching, appropriate light sources are applied in order to enhance the activity of the bleaching gels applied onto teeth. For this method to be effective, a high absorption of light within the gel is necessary. Variation in the light attenuation capability of the gel, the duration of application and light activation can contribute towards safety hazards associated with this procedure. Methods: In this study, seven different gels and hydrogen peroxide have been evaluated for their optical properties by means of spectrophotometry (440-1000 nm). The transmitted light spectrum was used to estimate the intensity loss for each gel. The mean intensity decreases observed were statistically analysed using an analysis of variance (ANOVA). Results: The five more-pigmented gels tested indicated a very similar intensity loss of around 80%, whereas the remaining two gels showed significantly less attenuation (predominantly, p < 10−6). Conclusions: Throughout the spectrum of wavelengths examined, and according to the underlying studies evaluated, five of the gels assessed demonstrated an attenuation high enough to possibly avoid overheating of the underlying enamel dentine and pulp. An evaluation of appropriate irradiation parameters is proposed.